Recommendations for a Framework for Handling Security Incidents of Electronic-Based Government Systems (SPBE) using the ISO/IEC 27035: 2023 Standard - Prastowo, Stefanus Lugas; Sudiana, Dodi (PT Mattawang Mediatama Solution, 2024)
The rapid development of Electronic Government Systems (EoBS) has brought significant improvements in the efficiency and accessibility of public services. However, the increasing reliance on these systems has also increased concerns about their security and the potential impact of security incidents on government operations and citizen trust. In order to address these challenges, this study proposes a framework for handling security incidents using the ISO/IEC 27035:2023 standard as a reference. The ISO/IEC 27035:2023 standard provides a comprehensive approach to incident management, covering the entire life cycle from preparation and identification to containment, eradication, and recovery. The recommended institution is the Ombudsman of the Republic of Indonesia, a government institution that carries out the function of overseeing the implementation of public services and receiving public complaints regarding alleged maladministration of public services. The preparation of the framework begins with a thorough analysis of the Ombudsman's existing security practices and potential threats to its electronic systems. This assessment is used as a basis for ensuring that the proposed solution is tailored to the specific needs and vulnerabilities of the institution. The stages carried out are preparation, identification, containment, eradication, recovery, and lessons learned. The recommendations produce a framework and insights that government agencies can use to adopt the ISO 27035:2023 standard. This study also shows that the implementation of the standard is relevant and in line with the SPBE policy in Indonesia.